Wysokie obcasy i konstrukcje tożsamości kobiet. Dynamika asymetrii płciowej, seksualności i emancypacji - Gromkowska-Melosik, Agnieszka (Studia Edukacyjne, 2019)
The article is devoted to the role of high heels in the construction of feminine identity. The various contexts of the main problem are analysed. The first one refers to the use of high heels as a confirmation of men’s domination over the feminine body, and identity. The second one is connected with sexual connotations of high heels. And the third one with the paradoxical use of the high heels as a source of women’s emancipation. The main thesis of the article is based on the assumption that every, even smallest feminine (or masculine) thing is involved into contradictory values and practical consequences.